2006
DOI: 10.1177/1059601106286888
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Individual Difference Factors Predicting Individuals’ Desire to Provide Upward Feedback

Abstract: This study examined the influence of several factors on employees’ desire to provide upward feedback to their supervisors on an impending upward feedback system. Self-report data from 153 university employees indicated that the desire to provide upward feedback related negatively to fear of retaliation and positively to role appropriateness, perceived usefulness, rater self-efficacy, leader-member exchange, knowledge of upward feedback, top management support, coworker support, and feedback-seeking behavior. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 57 publications
1
46
1
Order By: Relevance
“…So there must be constant, subtle "marketing" tied in with periodic contests or other splashes of 188 IJQRM 32,2 recognition if employee interest is to be maintained (Tatter, 1975;Fairbank and Williams, 2001;Kudisch, 2006;Neagoe and Klein, 2009;Marx, 1995;Prather and Turrell, 2002;Lloyd, 1996;Winter, 2009;Rapp and Eklund, 2007;Islam and Ismail, 2008;Reuter, 1976). The most common problems that organizations encounter with suggestion schemes are that there are too few useable suggestions.…”
Section: Publicitymentioning
confidence: 97%
See 1 more Smart Citation
“…So there must be constant, subtle "marketing" tied in with periodic contests or other splashes of 188 IJQRM 32,2 recognition if employee interest is to be maintained (Tatter, 1975;Fairbank and Williams, 2001;Kudisch, 2006;Neagoe and Klein, 2009;Marx, 1995;Prather and Turrell, 2002;Lloyd, 1996;Winter, 2009;Rapp and Eklund, 2007;Islam and Ismail, 2008;Reuter, 1976). The most common problems that organizations encounter with suggestion schemes are that there are too few useable suggestions.…”
Section: Publicitymentioning
confidence: 97%
“…et al (2010),Binnewies et al 2008),Arthur et al (2010),Binnewies et al (2007),Björklund (2010),Klijn and Tomic (2010),Kudisch (2006),McConville (1990),Ahmed (2009),Recht and Wilderom (1998), Tatter (1975),Khairuzzaman et al (2007),Fairbank and Williams (2001),Stranne (1964) 3CompetitionBakker et al (2006) 4 Effective systemReuter (1976),Lloyd (1996),Lloyd (1999),Marx (1995),McConville (1990),Fairbank et al (2003),Mishra (1994),Prather and Turrell, (2002), Eklund, (2007), Tatter, (1975), Van Dijk and Van Den Ende(2002), Arif et al (2010), Frese et al (1999), Hultgren (2008), Winter (2009), Fairbank and Williams (2001), Lloyd (1999), Basadur (Wilderom (1998), Lipponen et al (2008), Mclean (2005), Axtell et al (2000), Unsworth (2005) 7 Evaluation Rietzschel et al (2010), Neagoe and Klein (2009), Marx (1995), McConville (1990), Ahmed (2009), Tatter (1975), Van Dijk and Van den Ende (2002), Hultgren (2008), Lloyd (1996), Winter (2009), Fairbank and Williams (2001), Dean et al Erdem (2006), Bakker et al (2006), Buech et al (2010), Leach et al (2006), Mishra (1994), Rapp and Eklund (2007), Arif et al (2010), Hultgren (2008), Fairbank and Williams (2001), Stranne (1964), Basadur (1992), Van Dijk and Van den Ende (2002), Du plessis et al (2008), Verdinejad et al (2010) 10 Individual attributes and self efficacy Lipponen et al (2008), Verworn (2009), Frese et al (1999), Axtell et al (2000), Aoki (2008), Binnewies et al (2007), Björklund (2010), Griffiths-Hemans and Grover (2006), Klijn and Tomic (2010), Arthur et al (2010), Darragh-Jeromos (2005) 11…”
mentioning
confidence: 93%
“…A review of literature also reveals numerous rater-related factors which have influenced performance ratings: for example, raters' self-efficacy (see [11], self-monitoring (see [7], [8], [12], [13]) and rater trust or confidence in the appraisal system (see [8], [14]). A frequently studied factor is rater orientation to performance appraisal such as PAD (see [8] and [15]- [17].…”
Section: A Performance Appraisal System Studiesmentioning
confidence: 99%
“…It has been argued that raters' beliefs regarding their ability to rate accurately (i.e., rater self-efficacy, perceived ability to rate) will influence rating quality [11]. Studies have found raters with high self-efficacy tend to rate others more accurately than those with low self-efficacy (e.g., [7], [30], [31]).…”
Section: B Performance Appraisal Self-efficacy (Pase)mentioning
confidence: 99%
“…When the costs exceed the benefits of being in the relationship, individuals will end the relationship (Emerson, 1976). According to expectancy theory, individuals place a value on obtaining goals (Kudisch, Fortunato, & Smith, 2006). When an exchange partner obstructs the attainment of one's goals, the costs of being in that relationship are increased.…”
Section: Hypotheses Developmentmentioning
confidence: 99%